2021
DOI: 10.3390/ijms222011037
|View full text |Cite
|
Sign up to set email alerts
|

Astaxanthin Prevents Diet-Induced NASH Progression by Shaping Intrahepatic Immunity

Abstract: Dietary change leads to a precipitous increase in non-alcoholic fatty liver disease (NAFLD) from simple steatosis to the advanced form of non-alcoholic steatohepatitis (NASH), affecting approximately 25% of the global population. Although significant efforts greatly advance progress in clarifying the pathogenesis of NAFLD and identifying therapeutic targets, no therapeutic agent has been approved. Astaxanthin (ASTN), a natural antioxidant product, exerts an anti-inflammation and anti-fibrotic effect in mice in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 58 publications
0
11
0
Order By: Relevance
“…We and other researchers show that natural anti-oxidative and anti-inflammatory product astaxanthin can modulate intrahepatic and systemic inflammation and oxidative stress to inhibit NASH and liver fibrosis ( 120 ). Molecular mechanism study showed that metformin treatment inhibited the expression of IL-12-mediated proliferation, migration, and invasion of HCC cells and attenuated ectopic IL-22 expression-caused HCC progression by activating the Hippo signaling pathway ( 121 ).…”
Section: Treatmentsmentioning
confidence: 95%
“…We and other researchers show that natural anti-oxidative and anti-inflammatory product astaxanthin can modulate intrahepatic and systemic inflammation and oxidative stress to inhibit NASH and liver fibrosis ( 120 ). Molecular mechanism study showed that metformin treatment inhibited the expression of IL-12-mediated proliferation, migration, and invasion of HCC cells and attenuated ectopic IL-22 expression-caused HCC progression by activating the Hippo signaling pathway ( 121 ).…”
Section: Treatmentsmentioning
confidence: 95%
“…For example, the frequency of macrophages was increased in the NASH liver in amylin liver NASH (AMLN) diet-fed mice compared to that in standard chow diet-fed mice [ 15 ]. Our research study also showed that monocyte-derived macrophages increased in the liver of wild-type mice fed a choline-deficient, L-amino acid-defined, high-fat diet [ 16 ]. Other than that, adaptive immunity, including T cells such as the ratio of T helper (Th) cells/T regulatory cells (Tregs) and B cells, are activated or altered in the development of NAFLD [ 17 , 18 ].…”
Section: Introductionmentioning
confidence: 90%
“…Activation of HSCs, the major cells that contribute to liver fibrosis, is mediated by the activation of intrahepatic immunity during NASH. For example, proinflammatory cytokines such as TNF-α, transforming growth factor (TGF)-β1, and IL-1β expressed by intrahepatic macrophages can activate HSCs to promote the progression of liver fibrosis and NASH [ 16 ]. In contrast, a recent study showed that tissue-resident memory CD8 + T cells can trigger apoptosis of activated HSCs via Fas (TNF receptor superfamily, member 6)/FasL-mediated signaling [ 75 ].…”
Section: Intrahepatic Immunity In Nafld and Nash In Diet-induced Murine Models And Human Patientsmentioning
confidence: 99%
“…This is a unique feature that other models do not have, and it simulates some of the characteristics of human NAFLD. The CDAHFD model has significant applications in studying the role of novel therapeutic targets (such as TSP-1, transient receptor potential canonical (TRPC) 77 , 78 , traditional Chinese medicine (such as nobiletin, astaxanthin) 79 , 80 or western medicine (such as metformin and PPAR agonist) in NAFLD/NASH development 74 , 81 .…”
Section: Mouse Models Of Nafldmentioning
confidence: 99%